2009
DOI: 10.1111/j.1365-3083.2009.02262.x
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Active Toll‐Like Receptor 3 on Human Primary and Metastatic Cancer Cells

Abstract: Toll‐like receptor 3 (TLR3) is a member of Toll‐like receptors who recognize structurally conserved molecules derived from pathogens and trigger the immune response. To clarify if TLR3, is expressed in certain tumour cell lines and whether it is functional and what is the response of these cell lines to different concentrations of poly I:C treatment, we have screened SW480, SW620, FaDu and Detroit 562 cell lines using real‐time PCR, flow cytometry and ELISA. We have shown that all these cell lines express TLR3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…We have previously shown that poly(I:C) induced apoptosis in Detroit 562 cells [15]. We have shown that all chemotherapeutics tested combined with poly(I:C) increased the apoptosis of Detroit 562 cells when compared with using chemotherapeutics alone.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…We have previously shown that poly(I:C) induced apoptosis in Detroit 562 cells [15]. We have shown that all chemotherapeutics tested combined with poly(I:C) increased the apoptosis of Detroit 562 cells when compared with using chemotherapeutics alone.…”
Section: Resultsmentioning
confidence: 84%
“…The activation of TLR3, as well as of RIG-I, an MDA5, usually leads to type 1 IFN secretion. However, we and others have shown that poly(I:C) stimulation can also lead to IFN-γ secretion [15,16,17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…TLRs have been found to be overexpressed in certain pre-malignant conditions and neoplasia (25)(26)(27)(28), responsible for increasing angiogenic and metastatic potential of tumors activating nitric oxide synthase 2 and cyclooxygenase 2, and upregulating vascular endothelial growth factor and transforming growth factor-β within the tumor microenvironment (29)(30)(31). By contrast, TLRs can cause tumor inhibition (32)(33)(34)(35) and TLR ligands can have an anticancer effect, as demonstrated by studies on TLR7/8 and TLR9 agonists (36)(37)(38). In particular, TLR7 and TLR8 have emerged as key targets in immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…We have also observed TLR3 staining on lung squamous cell carcinoma and on a portion of HCC (our unpublished data). Furthermore, overexpression of TLR3 has been detected by flow c y t o m e t r y , b y w e s t e r n b l o t a n d / o r b y q P C R i n m e l a n o m a c e l l s [ 3 1 , 3 2 ] , e s o p h a g e a l squamous cell carcinoma [33], head and neck carcinoma cells [34] and multiple myeloma cells [35].…”
Section: Inflammatory and Proliferative Responses Of Cancer Cellsmentioning
confidence: 99%